Μετάφραση από τα αγγλικά προς τα ελληνικά της μελέτης του Ευρωπαϊκού Κοινοβουλίου με τίτλο: “Cross-border restitution claims of art looted in armed conflicts and wars and alternatives to court litigations” - (:unkn) unknown (My University, 2023)
Αντικείμενο της παρούσας εργασίας αποτελεί η μετάφραση από τα αγγλικά στα ελληνικά μέρους της μελέτης του Ευρωπαϊκού Κοινοβουλίου με τίτλο “Cross-border restitution claims of art looted in armed conflicts and wars and alternatives to court litigations” και ο σχολιασμός της μεταφραστικής διαδικασίας. Αρχικά, παρατίθεται το πρωτότυπο κείμενο στα αγγλικά και έπειτα το μετάφρασμα στα ελληνικά. Ύστερα, ακολουθεί ο σχολιασμός, στον οποίο εξετάζεται η μεταφραστική εντολή, σύμφωνα με τις λειτουργικές προσεγγίσεις των Nord και Vermeer (1997/2014), αναλύεται το κείμενο-πηγή σύμφωνα με τους ενδοκειμενικούς και εξωκειμενικούς παράγοντες της Nord (1991, σ. 15-124) ενώ στη συνέχεια προσεγγίζονται τα μεταφραστικά προβλήματα του κειμένου και οι στρατηγικές αντιμετώπισης τους σύμφωνα με τη Baker (1992, σ. 18-263) σε λεξικό, υπερλεξικό, πραγματολογικό και κειμενικό επίπεδο. Τέλος, εξετάζονται ζητήματα ορολογίας, ενώ στο παράρτημα της εργασίας επισυνάπτεται ένα γλωσσάρι με τους όρους του αρχικού κειμένου και τις αποδόσεις τους στα ελληνικά.

The subject of this thesis is the translation of a study from the European Commission from English to Greek titled “Cross-border restitution claims of art looted in armed conflicts and wars and alternatives to court litigations” and commentary on the translation process. The thesis includes the source text in English followed by the translated text in Greek. The commentary examines the translation commission according to functionalist approaches by Nord and Vermeer (1997/2014), followed by a source-text analysis that delves deep into Nord’s extratextual and intratextual factors (1991, p. 15-124). Following the analysis of the source-text, translation problems and strategies are discussed based on Baker’s approach (1992, p. 18-263), focusing on equivalence on word level and above-word level, as well as pragmatic and textual equivalence. Finally, terminology issues are analyzed. The thesis also includes a glossary containing terms from the source-text and their translation in Greek, which is attached at the end of the thesis.
Translation of a study from the European Commission from English to Greek titled “Cross-border restitution claims of art looted in armed conflicts and wars and alternatives to court litigations”
Keywords: μετάφραση, αγγλικά, ελληνικά, σχολιασμός, Ευρωπαϊκή Ένωση, λεηλασία έργων τέχνης, διεθνές δίκαιο, πρόληψη, απαγόρευση; translation, english, greek, commentary, European Union, art looting, international law, prevention, prohibition